2015
DOI: 10.1002/jcph.672
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Deficiency and Proton‐Pump Inhibitor Use: A Clinical Review

Abstract: The association of proton-pump inhibitor (PPI) use and hypomagnesemia has garnered much attention over the last 5 years. A large body of observational data has linked chronic PPI use with hypomagnesemia, presumably due to decreased intestinal absorption and consequent magnesium deficiency. However, despite the increasing prevalence of this highly popular class of medicine, and despite potential significant risks associated with magnesium depletion, including cardiac arrhythmias and seizures, there are no well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 51 publications
(55 reference statements)
2
35
0
2
Order By: Relevance
“…Mg serum concentration used as the single biomarker to diagnose Mg deficiency should be considered with caution also because Mg depletion in cells and bones can coexist with normal serum levels [7,32]. For example, Sales et al, in an animal study, observed that 70% dietary Mg restriction in association with increased fat intake resulted in reduced urinary Mg excretion and decreased bone Mg concentration without changes in plasma levels [33].…”
Section: Biomarkers For Assessment Of Mg Statusmentioning
confidence: 99%
“…Mg serum concentration used as the single biomarker to diagnose Mg deficiency should be considered with caution also because Mg depletion in cells and bones can coexist with normal serum levels [7,32]. For example, Sales et al, in an animal study, observed that 70% dietary Mg restriction in association with increased fat intake resulted in reduced urinary Mg excretion and decreased bone Mg concentration without changes in plasma levels [33].…”
Section: Biomarkers For Assessment Of Mg Statusmentioning
confidence: 99%
“…Although magnesium gluconate contains a large number of hydroxyl (OH) groups, the proton spectra of both the control and treated samples did not show any signal for the hydroxyl protons due to the replacement of the hydroxyl protons by deuterium from deuterated water, which was used as solvent for spectra recording. The signals for the protons coupling of CH 2 group and adjacent CH protons (2)(3)(4)(5) in the gluconic acid portion were observed in the control sample in the range of δ 3.46 to 4.02 ppm (Table 4), which was almost in accordance with the proton spectrum of sodium gluconate [48]. Consequently, the proton signals for CH 2 and CH groups for the treated sample were observed in the range of δ 3.44 to 4.01 ppm (Table 4).…”
Section: Nuclear Magnetic Resonance (Nmr) Analysismentioning
confidence: 99%
“…Magnesium gluconate, the organometallic salt of magnesium with gluconic acid, is useful for the prevention and treatment of many diseases such as cardiovascular diseases, diabetes mellitus, allergy, inflammatory diseases, immunological disorders, Alzheimer's disease, asthma, pre-eclampsia, eclampsia, cancer, oxidative stress induced ischemia/reperfusion injury, etc. [4][5][6][7][8][9]. It can be used as neuroprotective [10], an oral tocolytic agent [11], and also in a skin-tightening cosmetic composition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium gluconate is found to be a more powerful antioxidant than other magnesium salts and it is useful for the prevention and treatment of many diseases such as cardiovascular diseases, diabetes mellitus, allergy, inflammatory diseases, immunological disorders, Alzheimer's disease, asthma, pre-eclampsia and eclampsia, cancer, etc. [4][5][6][7][8]. It can be used as neuroprotective [9], for the treatment of oxidative stress induced ischemia/reperfusion injury [10] and also labor in women arrested initially with intravenous therapy as an oral tocolytic agent [11].…”
Section: Introductionmentioning
confidence: 99%